Perlawanan Bangsa Palestina Dalam Lagu Zalzil Amna Israel Karya Grup Nashid Fariq Wa’d ( Kajian Semiotika Charles Sander Pierce ): Palestinian Resistance in the Song "Zalzil Amna Israel" by the Nashid Group Fariq Wa’d (A Semiotic Study by Charles Sander Pierce) - Siregar, Saputra Husein; Fahriany (An-Nahdah Al-'Arabiyah, 2024)
This research is titled Resistance in the song Zalzil Amna Israel by Nashid Wa'd group, in the song Zalzil there are symbols of resistance that are called to the Palestinian people to the Israeli Zionist Occupiers, so, in this case, the author seeks to explain where the symbols of the signs that exist in the lyrics of the song Zalzil which shows the aesthetic resistance to Israel, by using Charles Sander Pierce's analytical knife as a means of dissecting the Zalzil song to find the meaning or sign of resistance in the lyrics of the Zalzil song, with the Triadic Concept or Charles Sander Pierce's triangle sign, namely: Representamen, Object, Intepretan. In simplifying the author uses descriptive analysis to identify the meaning of resistance in the lyrics. Penelitian ini berjudul Perlawanan dalam lagu Zalzil Amna Israel karya grup Nashid Wa’d, dalam lagu zalzil tersebut terdapat simbol tentang perlawanan yang di serukan kepada rakyat Palestina kepada para Penjajah Zionis Israel, maka dalam hal ini penulis berupaya menjelaskan dimana simbol-simbol tanda yang ada dalam lirik lagu Zalzil yang menunjukkan pada estetis perlawanan Kepada Israel, dengan menggunakan pisau analisanya Charles Sander Pierce sebagai sarana dalam membedah Lagu zalzil mencari makna atau tanda Perlawanan pada lirik Lagu Zalzil tersebut, dengan Konsep Triadic atau segitiga tandanya Charles sander Pierce yakni : Representamen, Objek, Intepretan. Dalam mempermudah penulis menggunakan analisis deskriptif untuk mengidentifikasi makna Perlawan dalam Lirik Tersebut